CD47 regulates antigen modulation and red blood cell clearance following an incompatible transfusion - Jajosky, Ryan P.; Covington, Mischa L.; Liu, Jun; Chai, Li; Zerra, Patricia E.; Chonat, Satheesh; Stowell, Sean R.; Arthur, Connie M. (Frontiers in Immunology, 2025)
Red blood cell (RBC) alloantibodies can result in the rapid removal of incompatible RBCs following transfusion. However, antibody-mediated clearance of RBCs is not the inevitable outcome of an incompatible transfusion. Antibody engagement can also result in the modulation of the target antigen, often rendering RBCs resistant to antibody-mediated removal. Despite this, the factors that regulate antibody-induced RBC removal or antigen modulation remain incompletely understood. Given the ability of CD47 to regulate RBC survival in general, we examined the possible role of CD47 in governing antibody-mediated RBC clearance and antigen modulation. This was achieved by crossing the well-established HEL-OVA-Duffy (HOD) mouse model with CD47 knockout (KO) mice to generate offspring that express the HOD antigen and either WT (HOD CD47 WT), heterozygote (HOD CD47 HET) or KO (HOD CD47 KO) levels of CD47. Using the commonly employed anti-HEL immunization model, our results demonstrate that while antibody engagement of HOD CD47 WT RBCs resulted in rapid antigen modulation in the absence of detectable RBC clearance, antibody binding to HOD CD47 HET RBCs did result in detectable RBC removal despite similar rates and overall levels of antigen modulation. In contrast, despite accelerated clearance of HOD CD47 KO RBCs in the absence of anti-HEL antibodies, the rate of RBC removal and antigen modulation was enhanced in the presence of anti-HEL antibodies. Taken together, these results suggest a role for CD47 in regulating the overall consequence of an incompatible RBC transfusion.